Character Strength and Happiness among Environmental and Educational Volunteers in a Collectivistic Culture - Fuad Nashori; Raden Rachmy Diana; Firdalaily Mahdanisa Zakie; Nadea Zulfa Khairunnisa (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
Volunteers participate in charitable activities sincerely without any certain expectations. Concerning this volunteerism, this study aims to investigate the influence of character strength on happiness in environmental and educational volunteers. Employing Seligman's happiness scale as a measurement instrument (Î± = 0.615) and Peterson and Seligman's (Î± = 0. 976) Value in Action - Inventory of Strength (VIA-IS) as a measurement instrument to determine character strength, 99 volunteers working in environmental and educational fields of voluntary organizations were recruited. The inclusion criteria for recruiting these participants included male or female participants over 18 years old, active at the organizations for at least six months, unmarried, and living in Yogyakarta. All obtained data were analyzed by using a Spearman correlation analysis technique and a regression analysis technique. The results of this study showed that some of the most influential types of character strength on happiness were leadership (r = 0.354, p = 0.000), appreciation of beauty and excellence (r = 0.337, p = 0.001), gratitude (r = 0.311, p = 0.002), forgiveness (r = 0.305, p = 0.002), and open-mindedness (r = 0.301, p = 0.002). In addition, types of character strength significantly influencing happiness are closely related to collectivistic culture.